The direct and spillover effects of liner shipping connectivity on merchandise trade. Issue 2 (25th April 2020) - Lin, Pei-Chun; Kuo, Szu-Yu; Chang, Jui-Hung
Abstract : Purpose: This paper aims to address the following questions: is good liner shipping connectivity a requisite for merchandise imports plus exports? What is the average of merchandise imports plus exports of the countries neighboring China? Do the merchandise imports plus exports of these countries correspond to each country's own merchandise imports plus exports or liner shipping connectivity index (LSCI)? Design/methodology/approach: The authors spatially analyze liner shipping connectivity and merchandise imports plus exports using 2016 data and a common framework for linear regression to establish the relationship amongst a country's LSCI and its merchandise imports plus exports and between its merchandise imports plus exports and those of its neighbors. Merchandise imports plus exports of countries are not necessarily independent of each other, and countries that are contiguous may produce similar observations. Findings: North America and Western Europe comprised clusters of countries that participated more actively in the international trading system, while Africa's countries had less international trade than average. The study identifies and quantifies the geographical ripple of transport infrastructure on merchandise trade from a national perspective. Notably, a spatially lagged term improved the model's ability to account for variations in merchandise imports plus exports across countries. Originality/value: The spatial lag of merchandise imports plus exports can contribute to specifying the spread of merchandise imports plus exports beyond what the authors would anticipate from a country's network of liner shipping.